Comparison of maxillary first molar occlusal outlines of Neandertals from the Meuse River Basin of Belgium using elliptical Fourier analysis - Williams Frank L’Engle; Lane Katherine M.; Anderson William G. (Anthropological Review, 2017)
Several Neandertals derive from the karstic caves of the Meuse river tributaries of Belgium, including Engis 2, Scladina 4A-4 and Spy 1. These may form a group that is distinct in maxillary first molar occlusal outlines compared to La Quina 5 from Southwest France. Alternatively, chronological differences may separate individuals given that Scladina 4A-4 from MIS 5 is older than the others from MIS 3. Neolithic samples (n = 42) from Belgium (Maurenne Caverne de la Cave, Hastière Caverne M, Hastière Trou Garçon, Sclaigneaux and Bois Madame) dated to 4.6–3.9 kyr provide a context for the Neandertals. Dental casts were prepared from dental impressions of the original maxillary molars. Crown and occlusal areas as well as mesiodistal lengths were measured by calibrated Motic 3.0 microscope cameras. Occlusal outlines of the casts were captured through photostereomicroscopy and non-landmark smooth tracing methods. Occlusal outlines were processed using elliptical Fourier analysis within SHAPE v1.3 which reduced amplitudes of the harmonics into principal components (PC) axes. The first two PC axes group the Neandertals, although Scladina 4A-4 falls nearly outside the convex hull for the Neolithic sample. Neandertals are imperfectly separated from the Neolithic sample on PC3 and PC4, and completely distinct on PC5 and PC6. Scladina 4A-4 differs from the other Neandertals on most PC axes. Chronology may best explain the separation of Scladina 4A-4 from the more recent fossils, and particularly Spy 1 and La Quina 5 which are the most similar in maxillary first molar occlusal outline shape.